2003
DOI: 10.1093/neuonc/5.2.96
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, phase 2 study of RMP-7 in combination with carboplatin administered intravenously for the treatment of recurrent malignant glioma

Abstract: RMP-7, a bradykinin analog, temporarily increases the permeability of the blood-brain tumor barrier to chemotherapy drugs like carboplatin. We conducted a randomized, controlled trial of carboplatin and RMP-7 versus carboplatin and placebo in patients with recurrent malignant glioma. The primary outcome measure was time to tumor progression (TTP). Adults with recurrent glioblastoma multiforme or anaplastic glioma were randomized in a 1:1 ratio to receive carboplatin and either RMP-7 or placebo. Radiation thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(87 citation statements)
references
References 9 publications
3
84
0
Order By: Relevance
“…Nevertheless, the percentage of patients with stable disease in our phase II study (38%) was comparable to prior single agent carboplatin trials [10,20]. The same applies for the median time to progression of 1.9 months observed in our study [22].…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the percentage of patients with stable disease in our phase II study (38%) was comparable to prior single agent carboplatin trials [10,20]. The same applies for the median time to progression of 1.9 months observed in our study [22].…”
Section: Discussionsupporting
confidence: 86%
“…Our recent clinical research showed that bradykinin B 2 receptors expression in glioma patients is positively correlated with the pathological grade of the glioma, but in each specific case, the expression pattern of B 2 receptors varies greatly [12]. The dose-dependent response to BK treatment suggests that the effect of BK treatment is correlated with the B 2 receptor expression level of the target cells; therefore we should screen patients according to their B 2 receptor expression levels in clinical RMP-7 trial study [13].…”
Section: Discussionmentioning
confidence: 99%
“…Another Phase II trial was conducted to investigate the effect in childhood high grade glioma and brainstem glioma, but also without effective results [135]. The lack of effectiveness in clinical trials has been attributed in part to the dose-limiting side effect of hypotension and to the differences between existing animal models and human patients [136]. The main drawback for the bradykinin analogs is that the effect of the receptors is exceedingly transient [127].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The main drawback for the bradykinin analogs is that the effect of the receptors is exceedingly transient [127]. Additionally, the non-uniform distribution of their receptors in the brain ultimately resulted in insufficient intracranial and intratumoral distribution of the anti-tumor compounds [136].…”
Section: Accepted Manuscriptmentioning
confidence: 99%